PENGARUH RESIKO BISNIS, PERTUMBUHAN ASSET, PROFITABILITAS DAN KEPEMILIKAN MANAJERIAL TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI BEI PERIODE TAHUN 2009 – 2011 (Students' Journal of Economic and Management, 2014)
Capital structure is counter balance between capital use self with long-range loan use, the purpose how big capital self and how big long term liabilities that be used, so that can optimal. with optimal capital structure existence will produce optimal rate of return also, so that merely company that get profit, but stockholder even also come along to get profit. (farah margaretha, 2003). This watchfulness aims to test business risk influence, asset growth, profitability, and property manajerial towards capital structure in manufacturing business at indonesian Stock exchange period 2009 - 2011. population that used in this watchfulness manufacturing business go public during 3 year that is begins year 2009 -2011. with take sample has companied that listed at indonesia effect exchange (bei). as to sample taking is chosen according to purposive sampling got 77 emiten.This watchfulness result shows that negative influential business risk and significant towards capital structure. while asset growth, profitability, and property manajerial positive influential and significant towards capital structure.Keyword : business risk, asset growth, profitability, property manajerial, and capital structure